Cranial Bone Transport Promotes Angiogenesis, Neurogenesis, and Modulates Meningeal Lymphatic Function in Middle Cerebral Artery Occlusion Rats. Issue 4 (9th February 2022) - Bai, Shanshan; Lu, Xuan; Pan, Qi; Wang, Bin; Pong U, Kin; Yang, Yongkang; Wang, Haixing; Lin, Sien; Feng, Lu; Wang, Yan; Li, Yucong; Lin, Weiping; et al.
Abstract : Background: Ischemic stroke is a leading cause of death and disability worldwide. However, the time window for quickly dissolving clots and restoring cerebral blood flow, using tissue-type plasminogen activator treatment is rather limited, resulting in many patients experiencing long-term functional impairments if not death. This study aims to determine the roles of cranial bone transport (CBT), a novel, effective, and simple surgical technique, in the recovery of ischemic stroke using middle cerebral artery occlusion (MCAO) rat model. Methods: CBT was performed by slowly sliding a bone segment in skull with a special frame and a speed of 0.25 mm/12 hours for 10 days following MCAO. Morris water maze, rotarod test, and catwalk gait analysis were used to study the neurological behaviors, and infarct area and cerebral flow were evaluated during CBT process. Immunofluorescence staining of CD31 and Nestin/Sox2 (sex determining region Y box 2) was performed to study the angiogenesis and neurogenesis. OVA-A647 (ovalbumin-Alexa Fluor 647) was intracisterna magna injected to evaluate the meningeal lymphatic drainage function. Results: CBT treatment has significantly reduced the ischemic lesions areas and improved the neurological deficits in MCAO rats compared with the rats in the control groups. CBT treatment significantly promoted angiogenesis and neurogenesis in the brain of MCAO rats. The drainage function of meningeal lymphatic vessels in MCAO rats was significantly impaired compared with normal rats. Ablation of meningeal lymphatic drainage led to increased neuroinflammation and aggravated neurological deficits and ischemic injury in MCAO rats. CBT treatment significantly improved the meningeal lymphatic drainage function and alleviated T-cell infiltration in MCAO rats. Conclusions: This study provided evidence for the possible mechanisms on how CBT attenuates ischemic stroke injury and facilitates rapid neuronal function recovery, suggesting that CBT may be an alternative treatment strategy for managing ischemic stroke.